Feasibility, Acceptability, and Preliminary Impact of an Online Latina Mother–Daughter Physical Activity Intervention - Elva M. Arredondo; Jennifer L. Schneider; Marisa S. Torres-Ruiz; Victoria M. Telles; Katie Butte; Oliva Lafuente; Taynara Formagini; Athena Cisneroz; Scott C. Roesch; Tom Baranowski; Guadalupe X. Ayala (Journal of Physical Activity and Health, 2026)
Background : Latina girls have low rates of moderate to vigorous physical activity (PA) compared with their male counterparts and non-Hispanic White girls. The current study examines the feasibility, acceptability, and preliminary impact of Conmigo , a mother–daughter PA intervention for preadolescent Latinas (ages 8–11) delivered online. Methods : Seventy-nine mother–daughter dyads were recruited. Dyads were randomized to a PA intervention or a delayed, abbreviated control condition. The PA intervention consisted of 12 weekly 1.5-hour virtual PA sessions. Feasibility was measured by the delivery, receipt, and enactment of the intervention; acceptability was measured by satisfaction in surveys and interviews in the PA intervention condition. PA and associated secondary outcomes were measured at baseline and follow-up (12 wk) using accelerometry and self-report. Results : Most mothers had some college education (63.3%), and 44.3% worked full time; most daughters were US-born (91.1%) compared with mothers (38.0%). Program fidelity was high (81%–95%) with a mean attendance of 6.2 (SD = 4.6) across 12 sessions. Satisfaction was high (mean = 4.6, SD = 0.8). Qualitative findings indicated that the curriculum met families’ needs. No significant changes were observed in daughters’ accelerometer-assessed or self-reported PA. A marginal improvement ( B = 0.37, P < .05) was found in limit-setting behavior; other parenting outcomes and dyadic effects were nonsignificant. Conclusions : Qualitative and quantitative findings were not fully aligned regarding feasibility, acceptability, and preliminary impact of the online Conmigo program. Nonetheless, online mother–daughter PA interventions may represent a scalable strategy to have high reach among Latino families.